2003
DOI: 10.1051/ata/2003014
|View full text |Cite
|
Sign up to set email alerts
|

Stupéfiants et conduite automobile - les actions réalisées en Belgique

Abstract: RÉSUMÉ En mars 1999 une nouvelle loi réprimant la conduite sous influence de drogues illicites a été introduite en Belgique. La procédure légale consiste en a) un test de comportement, b) un dépistage immunochimique pour 4 groupes de drogues dans les urines c) une confirmation par une analyse du plasma (GC-MS avec des seuils fixes SUMMARY In March 1999 a new law prohibiting driving while impaired by illegal drugs was introduced in Belgium. The legal procedure consists of a) a field impairment test, b) a urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
6
1
1
Order By: Relevance
“…Detection of this group depends on the perception of the police officers and additionally there are remarkable differences between countries, probably because of different national road traffic acts and levels of attention to the problem. The prevalence for COC abuse in the present study is higher than in most other reports with a rate between 0.1 and 8.4% [37][38][39][40][41][42][43][44][45][46][47][48], but in the US [49,50], Belgium [51,52], the Netherlands [53], Switzerland [54], and Germany [36,55] a higher prevalence was found between 10.2 and 32.7%.…”
Section: Discussioncontrasting
confidence: 71%
“…Detection of this group depends on the perception of the police officers and additionally there are remarkable differences between countries, probably because of different national road traffic acts and levels of attention to the problem. The prevalence for COC abuse in the present study is higher than in most other reports with a rate between 0.1 and 8.4% [37][38][39][40][41][42][43][44][45][46][47][48], but in the US [49,50], Belgium [51,52], the Netherlands [53], Switzerland [54], and Germany [36,55] a higher prevalence was found between 10.2 and 32.7%.…”
Section: Discussioncontrasting
confidence: 71%
“…The prevalence of in the present study is higher than in most other reports, with a rate between 0 and 7% (15,23–38), but in Australia (39), Belgium (40), the Netherlands (41), Norway (42), and Germany (43,44), a similar prevalence was found of amphetamine abuse between 19.7 and 29.3%. In Sweden (45) and also in a study from Belgium (46), the prevalence was actually reported with 59.0 and 54.2%, respectively. It has to be taken into consideration that a positive preselection was made in all of these studies.…”
Section: Discussionmentioning
confidence: 80%
“…In Belgium, 18% tested positive to COC in a sample of drivers. 20 In Germany, 21 13% were found to have COC in samples taken from road traffic users. Most incidents were between the hours of evening and early morning on Saturdays and Sundays.…”
Section: Discussionmentioning
confidence: 99%